Promoting Physiological Transformations in Cinema (Al-Academy, 2023)
Cinema has always addressed human issues from diverse perspectives. It covered biographies, philosophy, history, war, and sci-fi. These disciplines promote economic and artistic success. Since the 1930s, cinema has explored sexual transformation. These films have defended homosexuals, explored how homosexuality causes AIDS, and discussed transgenderism for decades. As widely recognised, animated films for adults and children worldwide have included this trend. This study will demonstrate how hormone imbalance affects sexual function. This study, "Promoting Physiological Transformations in Cinema," comprises four chapters: The first chapter (methodological framework) covers the study problem, "What are the foundations and necessities of physiological transformation processes in cinema?" Thus, the importance, need, goal, and limitations of the study Physiology: origin and concept, psychology's role in physiological transformation, and the Danish Girl's advocacy for physiological transformation were included in the second chapter (theoretical framework and prior investigations). The third chapter included results, conclusions, recommendations, suggestions, and references.